Caspase Inhibition Affects the Expression of Autophagy-Related Molecules in Chondrocytes - Vesela, Barbora; Svandova, Eva; Ramesova, Alice; Kratochvilova, Adela; Tucker, Abigail S; Matalova, Eva (Cartilage, 2021)
Objective. Caspases, cysteine proteases traditionally associated with apoptosis and inflammation, have recently been identified as important regulators of autophagy and reported within the growth plate, a cartilaginous part of the developing bone. The aim of this research was to identify novel autophagy-related molecules affected by inhibition of pro-apoptotic caspases in chondrocytes. Design. Chondrocyte micromasses derived from mouse limb buds were treated with pharmacological inhibitors of caspases. Autophagy-related gene expression was examined and possible novel molecules were confirmed by real-time polymerase chain reaction and immunocytofluorescence. Individual caspases inhibitors were used to identify the effect of specific caspases. Results. Chondrogenesis accompanied by caspase activation and autophagy progression was confirmed in micromass cultures. Expression of several autophagy-associated genes was significantly altered in the caspases inhibitors treated groups with the most prominent decrease for Pik3cg and increase of Tnfsf10. The results showed the specific pro-apoptotic caspases that play a role in these effects. Importantly, use of caspase inhibitors mimicked changes triggered by an autophagy stimulator, rapamycin, linking loss of caspase activity to an increase in autophagy. Conclusion. Caspase inhibition significantly affects regulation of autophagy-related genes in chondrocytes cultures. Detected markers are of importance in diagnostics and thus the data presented here open new perspectives in the field of cartilage development and degradation.
Keywords: autofagie; gene expression; Chondrocytes; limb; inhibitory kaspas; caspase; chondrogeneze; Caspases; kaspasy; Caspase Inhibitors; autophagy; Animals; Autophagy; chondrocyty; inhibition; Chondrogenesis; zvířata; myši; Mice